Multidimensional performance characteristics in selected and deselected talented soccer players - Huijgen, B. C. H.; Elferink-Gemser, M. T.; Lemmink, K. A. P. M.; Visscher, C. (European Journal of Sport Science, 2014)
The present study examined whether performance characteristics discriminated between selected and deselected players in talent development programmes. This examination was carried out in talented soccer players, aged 16-18 years using objective measurement instruments. Four domains of multidimensional performance characteristics (physiological, technical, tactical and psychological) were assessed by using a test battery consisting of soccer-specific field tests and questionnaires. Multivariate analyses of covariance revealed that the physiological characteristics peak and repeated shuttle sprint, the technical characteristics of peak and repeated shuttle dribble and the tactical characteristic of `positioning and deciding`, significantly differed between the selected (n=76) and deselected players (n=37), with selected players performing better (P<0.05). Discriminant function analysis showed that the combination of the technical characteristic `peak dribbling`, the tactical characteristic `positioning and deciding` and the physiological characteristic of `peak sprinting` classified 69% of talented players correctly. In conclusion, the decisions made by the investigated clubs to either select or deselect players in their talent development programme, whom were aged 16-18 years, were mostly discriminated by aspects of the players' technical, tactical and physiological skill performances. Sports research can play an essential role in investigating the club's perception of important performance characteristics in talented players.